Presentation of CS-Map Results for Guinayangan, Quezon - Gutierrez, Mary Anne; Raviz, Jeny; Garcia, Cornelia; Castillo, Rowena; Laborte, Alice (International Rice Research Institute, 2024)
In partnership with the International Institute of Rural Reconstruction (IIRR) and the local government of Guinayangan, Quezon, the CGIAR Research Initiative on Climate Resilience (ClimBeR) has implemented the Climate-Smart Mapping and Adaptation Planning (CS-MAP) in 10 barangays of Guinayangan, Quezon. CS-MAP, a participatory mapping approach developed by CCAFS-SEA, is designed to assess climate-related risks, identify vulnerable areas, and create location-specific adaptation plans. This presentation shares preliminary findings with Guinayangan’s partners and stakeholders, including climate risk maps and consolidated adaptation plans, and aims to integrate of climate-smart practices into local agricultural planning and decision-making.